Reconstructing the May Fourth Movement: the role of communication, propaganda, and international actors - Wagner, Rudolf G. (The journal of transcultural studies, 2021)
The May Fourth Movement is a key element in the master narrative of Chinese modernity. The ingredients of this narrative have mostly come from the protagonists of this movement themselves, with few challenges coming from later scholarship. Collectively, these narratives have largely encased the May Fourth Movement into a nation-state historiography. The transcultural dimension of the May Fourth New Culture and the political movement has been left out or largely marginalized. This article centers on the international nature of the May Fourth political movement by focusing on the crucial role played by foreign actors and their impact on communication and propaganda in particular. It argues that The May Fourth Movement had to compensate for a strong asymmetry in the available means of communication, information, and propaganda related to Japan and the Western powers. The movement successfully compensated by relying on foreign participants who were sympathetic to its goals, nationally and internationally informed, and connected and active in media communications. These foreigners were constituent to and accepted by this movement. They provided guidance and information, and circulated international propaganda. If we define the May Fourth political agenda as self-determination for China and a struggle against Japanese control, we can see an active involvement by this group of foreigners who were committed to Chinese interests rather than their own country’s shifting policies.